Lignin phenols in sediments of Lake Baikal, Siberia: application to paleoenvironmental studies - Orem, W. H.; Colman, S. M.; Lerch, H. E. (Organic Geochemistry, 1997)
Sediments from three cores obtained from distinct depositional environments in Lake Baikal, Siberia were analyzed for organic carbon, total nitrogen and lignin phenol concentration and composition. Results were used to examine changes in paleoenvironmental conditions during climatic cycles of the late Quaternary (<125 ka). Average organic carbon, and total nitrogen concentrations, atomic C/N ratios and organic carbon accumulation rates were significantly higher in the Holocene compared with the late Pleistocene, reflecting overall warmer temperatures and increased runoff during the Holocene. A Holocene maximum in organic carbon was observed at about 6 ka, and may represent the warmest/wettest period of the Holocene. At one site (Academician Ridge) pronounced late Pleistocene maxima in organic carbon and biogenic silica were observed at about 80-85 ka, probably indicative of an interstadial period with enhanced aquatic productivity. Total sedimentary lignin phenol contents were generally lower in the late Pleistocene compared to the Holocene, but with several peaks in concentration during the late Pleistocene. These late Pleistocene peaks in total sedimentary lignin content (dated at about 80, 50 and 30 ka) directly precede or occur during peaks in sedimentary biogenic silica contents. These periods likely represent relatively warm interstadial times, with increased precipitation producing the observed increase in terrestrial runoff and aquatic productivity. Lignin phenol ratios (S/V, C/V and P/V) were used to examine changes in terrestrial vegetation type resulting from changes in paleoenvironmental conditions during the late Pleistocene. A degree of caution must be used in the interpretation of these ratios with regard to vegetation sources and paleoenvironmental conditions, because of potential compositional changes in lignin resulting from biodegradation. Nevertheless, results show that long glacial periods were characterized by terrestrial vegetation composed of a mix of non-woody angiosperm vegetation and minor gymnosperm forest. Shorter interstadial periods are defined by a change to dominant gymnosperm forest and were observed at about 80, 75, 63, 50 and 30 ka, ranging from about 2-6 kyr in duration. These interstadial periods of the late Pleistocene defined by lignin phenol ratios generally occur during longer periods of enhanced sedimentary biogenic silica content (about 10-15 ka in duration), providing corroborative evidence of these warm interstadial periods. (C) 1997 Elsevier Science Ltd.
Yq252Times Cited:29Cited References Count:61